The shadows we know by heart - Park, Jennifer 1977- (Simon Pulse, 2017)
Leah Roberts has been secretly watching sasquatches in the woods behind her house for years, but when she notices an enigmatic teenage boy living among them, her complicated family life starts to unravel
Keywords: JUVENILE FICTION / Fairy Tales & Folklore / General / bisacsh; JUVENILE FICTION / Animals / Mythical / bisacsh; JUVENILE FICTION / Family / General (see also headings under Social Issues) / bisacsh; Sasquatch; Secrets; Family problems; Love; Animals, Mythical; JUVENILE FICTION / Fairy Tales & Folklore / General; JUVENILE FICTION / Animals / Mythical; JUVENILE FICTION / Family / General (see also headings under Social Issues); Liebe; Schneemensch; Geheimnis; Familienkonflikt; Jugendbuch